From gr8 to great: Lexical Access to SMS Shortcuts - Ganushchak, Lesya; Krott, Andrea; Meyer, Antje S. (Frontiers in Psychology, 2012)
Many contemporary texts include shortcuts, such as cu or phones4u. The aim of this study was to investigate how the meanings of shortcuts are retrieved. A primed lexical decision paradigm was used with shortcuts and the corresponding words as primes. The target word was associatively related to the meaning of the whole prime (cu/see you - goodbye), to a component of the prime (cu/see you - look), or unrelated to the prime. In Experiment 1, primes were presented for 57 ms. For both word and shortcut primes, responses were faster to targets preceded by whole-related than by unrelated primes. No priming from component-related primes was found. In Experiment 2, the prime duration was 1000 ms. We replicated the priming effects of Experiment 1. Additionally, there was priming from component-related word primes, but not from component-related shortcut primes. These results indicate that the meanings of shortcuts can be retrieved without translating them first into corresponding words.